PERANCANGAN BUKU TRAVEL GUIDE WISATA BELANJA GROSIR PAKAIAN DI KOTA SURABAYA BERBASIS FOTOGRAFI SEBAGAI SARANA INFORMASI INSTITUT BISNIS DAN INFORMATIKA STIKOM SURABAYA - Hidayah, Maula; Riyanto, Darwin Yuwono; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
The purpose of designing a city guide book wholesale clothing shopping Surabaya based photography as a means of information. To give an information about wholesale shopping city of Surabaya. Further studies conducted using qualitative research methods are observation, interviews, documentation, and literature. To obtain the data used and supports the creation of a shopping travel city guide book wholesale clothing Surabaya based photography as a means of information. Data were analyzed using multiple stages, namely data reduction, data presentation and conclusion. After analyzing the data, found a city guide book concept shopping wholesale clothing Surabaya based photography as a means of information. Keyword "Elegant", description "Elegant Elegant, neat, elegant, graceful, supple. The main concept of the book itself is a travel guide book wholesale clothing shopping Surabaya-based photography to illustrate the location, atmosphere, and photos of activities that are in the market. The concept of "Elegant" aims to illustrate the location, atmosphere, and photos of activities that are in the market. Kata Kunci : Buku Travel Guide, Berbasis Fotografi, Wisata Belanja Grosir, Kota Surabaya.